3D Printing for Electrochemical Energy Applications - Browne, Michelle P; Redondo, Edurne; Pumera, Martin (Chemical reviews, 2020)
Additive manufacturing (also known as three-dimensional (3D) printing) is being extensively utilized in many areas of electrochemistry to produce electrodes and devices, as this technique allows for fast prototyping and is relatively low cost. Furthermore, there is a variety of 3D-printing technologies available, which include fused deposition modeling (FDM), inkjet printing, select laser melting (SLM), and stereolithography (SLA), making additive manufacturing a highly desirable technique for electrochemical purposes. In particular, over the last number of years, a significant amount of research into using 3D printing to create electrodes/devices for electrochemical energy conversion and storage has emerged. Strides have been made in this area; however, there are still a number of challenges and drawbacks that need to be overcome in order to 3D print active and stable electrodes/devices for electrochemical energy conversion and storage to rival that of the state-of-the-art. In this Review, we will give an overview of the reasoning behind using 3D printing for these electrochemical applications. We will then discuss how the electrochemical performance of the electrodes/devices are affected by the various 3D-printing technologies and by manipulating the 3D-printed electrodes by post modification techniques. Finally, we will give our insights into the future perspectives of this exciting field based on our discussion through this Review.